Pengaruh Literasi Keuangan, Overconfidence, dan Herding Behavior Terhadap Keputusan Mahasiswa Akuntansi di Surakarta - Samuel Bagus Kristiawan; Rispantyo Rispantyo (Pusat Riset dan Inovasi Nasional, 2026)
This study examines the influence of financial literacy, overconfidence, and herding behavior on the investment decision-making process among accounting students in Surakarta. Investment decisions in the student demographic are not merely a product of technical financial proficiency; they are significantly shaped by psychological and social factors that dictate behavioral patterns in instrument selection. While financial literacy serves as a critical cognitive foundation for interpreting complex financial concepts, psychological traits such as overconfidence and social tendencies like herding behavior can potentially induce biases or irrationality in investment practices. Adopting a quantitative methodology, this research utilizes primary data gathered through structured questionnaires distributed to accounting students in Surakarta. The sample was determined via purposive sampling, with data processed through multiple linear regression analysis using SPSS software. The empirical findings reveal that financial literacy exerts a positive and significant impact on the quality of investment decisions. Furthermore, overconfidence was found to have a positive correlation, while herding behavior also emerged as a significant determinant of student investment choices. These results underscore that the combination of financial knowledge and behavioral variables is instrumental in enhancing the efficacy of investment decision-making among accounting students